Message - Oluwatoyin, Dr. DANIYAN, Michael (Universal Journal of Pharmaceutical Research, 2022)
According to WHO 2020 reports, 10 top global deadliest diseases in 2019, which includeIschemic heart disease, or coronary artery disease (15.5%), Stroke (11.1%), Lower respiratory infections (5.7%), Chronic obstructive pulmonary disease (5.6%), Trachea, bronchus, and lung cancers (3%), Diabetes mellitus (2.8%), Alzheimer’s disease and other dementias (2.7%), Dehydration due to diarrheal diseases (2.5%), Tuberculosis (2.4%), and Cirrhosis (2.1%), accounted for 55% of the 55.4 million deaths worldwide. In Africa, malaria is still a serious factor to reckon with, accounting for 229 million cases and 409,000 deaths globally in 2019. However, the arrival of COVID-19 has changed the dynamics of disease control and management, widening the long standing gaps among income classes, disrupting access to critical health services and medicine, and threatening our capacity to maintain already attained gains against these diseases in recent decades, as well as our targets for attaining sustainable development goals. While COVID-19 remains, these other diseases are not by any means in a hurry to disappear. In fact, they feel more at home than ever before, and may possibly have developed new survival strategies. Thus, COVID-19 has senior brethren.Co-morbidity with these deadly diseases is also not uncommon. Global economy has also been affected, leading to massive reduction in funding to sustain actions against these other deadly diseases, and to propel research aimed at providing solutions. With disruption to supply or access to essential medicines, increases in the development of resistance to drugs by infectious agents may be on the increase. Meanwhile, despite the challenges posed by COVID-19, the global response to this deadly pandemic comes with some lessons that can be applied to tackle the problem occasioned byother deadly diseases. Briefly, COVID-19 has brought to limelight the essential roles of research community in providing solutions to human problems, and the need for synergy among stakeholders, including academia, policy makers, industrialists, health professionals, among others. Also, COVID-19 has provided opportunities for researchers to think globally outside the box, reaching out beyond ones locality in search for solution to research questions. Furthermore, it provides opportunities to revisit abandoned or currently in use options, for the sole aim of repurposing or reengineering for the good of mankind. It provides opportunity to use / adapt research resources and control protocols that have been deployed to tackle COVID-19 for use in tackling or stemming the spread of these diseases. As it were with COVID-19, all known deadly diseases should now be treated as an emergency, requiring urgent attention with prompt information dissemination. Importantly, engaging in and encouraging more open access publications will enhance access to research data and fast-track the discoveries of potent solutions. In this regard, Universal Journal of Pharmaceutical Research (UJPR) encourages open access publications and provides a platform for the dissemination of your research outputs on every aspect of pharmaceutical and related biomedical sciences. The UJPR is indexed in Copernicus, J-Gate, CAS, NCBI, CASSI, Publons, EuroPub, CrossRef, Directory of Science, among others. With seasoned editorial board members, who are experts in different fields of pharmaceutical and biomedical sciences, UJPR peer-review process is very thorough and fast enough for your articles to be appreciated bimonthly.